Analysis of Biology Students' Multiple Intelligences as a Basis for Modifying Teaching Methods - Selaras, Ganda Hijrah; Lufri, Lufri; Alberida, Heffi; Iswari, Mega; Afdal, Afdal; Sepriadi, Ilham (Bioeducation Journal, 2024)
Education is an important effort in creating a conducive learning atmosphere and learning process for students. In the process, educators who do not understand the intelligence of students will have difficulty facilitating the process of developing individual potential to realize their goals. intelligence is the ability to solve problems and create products that have cultural value. The intelligence possessed by students varies, or is also known as multiple intelligences. Multiple intelligence consists of nine types of intelligence which include: 1) logical-mathematical intelligence, 2) naturalistic intelligence, 3) musical intelligence, 4) verbal intelligence, 5)interpersonal intelligence, 6) bodily kinesthetic intelligence, 7) intrapersonal intelligence, 8) intelligence spatial-visual, and 9) existential. This research is a quantitative descriptive study conducted on 218 students of the biology department of UNP in 2022. It is hoped that this research will help educators to be able to design effective learning processes in accordance with the intelligence criteria of students.